2013
DOI: 10.1007/s11103-013-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

GmNFYA3, a target gene of miR169, is a positive regulator of plant tolerance to drought stress

Abstract: Nuclear factor Y (NF-Y) is a heterotrimeric transcription factor composed of NF-YA, NF-YB and NF-YC proteins. In this study, we identified and characterized a gene, GmNFYA3, which encodes the NF-YA subunit of the NF-Y complex in soybeans (Glycine max L.). Real time RT-PCR analysis indicated that GmNFYA3 was induced by abscisic acid (ABA) and abiotic stresses, such as polyethylene glycol, NaCl and cold. Subcellular localization analysis suggested that GmNFYA3 may activate its specific targets in the nucleus. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
202
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(211 citation statements)
references
References 43 publications
9
202
0
Order By: Relevance
“…Overexpression of TaNFYA-B1 Promotes Wheat Growth and Grain Yield NF-Y transcription factors have been shown to improve drought tolerance in Arabidopsis , maize (Nelson et al, 2007), and soybean (Glycine max; Ni et al, 2013) and to reduce N starvation-induced senescence in Arabidopsis (Leyva-González et al, 2012). Here, we found that overexpressing TaNFYA-B1 improved N uptake, P uptake, and grain yield in wheat Figure 6.…”
Section: Nf-y Genes In Wheat Respond Variously To N and P Starvationmentioning
confidence: 63%
See 1 more Smart Citation
“…Overexpression of TaNFYA-B1 Promotes Wheat Growth and Grain Yield NF-Y transcription factors have been shown to improve drought tolerance in Arabidopsis , maize (Nelson et al, 2007), and soybean (Glycine max; Ni et al, 2013) and to reduce N starvation-induced senescence in Arabidopsis (Leyva-González et al, 2012). Here, we found that overexpressing TaNFYA-B1 improved N uptake, P uptake, and grain yield in wheat Figure 6.…”
Section: Nf-y Genes In Wheat Respond Variously To N and P Starvationmentioning
confidence: 63%
“…Several studies suggested that members of the NF-Y family play essential roles in the control of flowering (Kumimoto et al, 2008(Kumimoto et al, , 2010Wei et al, 2010;Li et al, 2011;Yan et al, 2011), seed development (Yamamoto et al, 2009), photosynthesis (Stephenson et al, 2010(Stephenson et al, , 2011, and nodule development (Combier et al, 2006(Combier et al, , 2008Zanetti et al, 2010). Other NF-Y family members are known to enhance tolerance to abiotic stresses such as drought (Nelson et al, 2007;Stephenson et al, 2007;Li et al, 2008;Ni et al, 2013), salinity (Zhao et al, 2009;Leyva-González et al, 2012), and cold (Leyva-González et al, 2012;Shi et al, 2014). A relationship between NF-Ys and N utilization was first reported in yeast: the HAP complex regulates the expression of Glucose dehydrogenase1 and an N-starvationspecific gene, vacuolar serine protease (isp6 + ; Dang et al, 1996;Nakashima et al, 2002;Riego et al, 2002).…”
mentioning
confidence: 99%
“…[57] NF-Y is also known as heme-activated protein or CCAAT-binding factor. Moreover, CCAAT box is present in about 25% of eukaryotic gene promoters.…”
Section: ããmentioning
confidence: 99%
“…Moreover, CCAAT box is present in about 25% of eukaryotic gene promoters. [57,58] Over-expression of NFYB1 in Arabidopsis and maize conferred significantly increased drought resistance. [59] In drought stress, expression of NF-Y genes appears to be decreased in wheat leaves.…”
Section: ããmentioning
confidence: 99%
“…Additionally, Arabidopsis AtNF-YA3 and AtNF-YA8 were also found as redundant genes required in early embryogenesis of plants [11]. In soybean, overexpression of GmNF-YA3 conferred the reduction of leaf water loss and enhanced drought tolerance in transgenic Arabidopsis plants [12].…”
Section: Introductionmentioning
confidence: 99%